Drivers of Continuing Education Learning Preferences for Veterans Affairs Women's Health Primary Care Providers. Issue 3 (2017) - Zuchowski, Jessica L.; Hamilton, Alison B.; Washington, Donna L.; Gomez, Arthur G.; Veet, Laure; Cordasco, Kristina M.
Abstract : Introduction: Documented gaps in health professionals' training in women's health are a special concern for continuing education (CE). In the Veterans Affairs (VA) health care system, women veterans are a numerical minority, preferably assigned to designated women's health primary care providers (DWHPs). DWHPs need to maintain their knowledge and skills in women's health topics, in addition to general internal medicine topics. We explored drivers of VA DWHPs' learning preferences for women's health topics—ie, factors which influence greater and lesser learning interest. Methods: We conducted semistructured telephone interviews with DWHPs across six VA health care systems. Interviews were audio recorded, transcribed, and coded in ATLAS.ti. We synthesized results by grouping relevant coded sections of text to form emergent themes. Results: Among the 31 DWHPs interviewed, reported drivers of learning interests among women's health topics were (1) high frequency of clinical incidence of particular issues; (2) perceived appropriateness of particular issues for management in primary care settings; and (3) perceived appropriateness of particular issues for partial management in primary care. Lower interest in particular women's health topics was associated with (1) perceived existing competency or recent training in an issue and (2) perceived need for specialty care management of an issue. Discussion: Understanding drivers of DWHPs' CE learning priorities lays a foundation for developing CE programming that will be of interest to women's health primary care providers. Attention to drivers of learning interests may have applicability beyond women's health, suggesting a general approach for CE programming that prioritizes high-volume topics within the practice scope of target providers.